Estudo das condições reacionais da reação de clivagem oxidativa de β-hidróxi éteres bicíclicos promovida por tetróxido de rutênio Study of the conditions of the ruthenium tetraoxide-promoted oxidative cleavage reaction of bicyclic β-hydroxy ethers - Helena M. C. Ferraz; Alexsandra C. Scalfo; Bruno T. Vilalba; Luiz S. Longo Jr (Química Nova, 2010)
A systematic study of the reaction of β-hydroxy ethers with ruthenium tetraoxide (RuO4), generated in situ from ruthenium trichloride and sodium periodate, is presented, leading to nine-membered ring keto-lactones in moderate yields. Three different solvent systems - AcOEt/MeCN/H2O, MeCN/H2O and DMC/H2O - were studied leading to the desired products in lower yields than those obtained with the classical mixture of CCl4/MeCN/H2O, commonly used in reactions promoted by this oxidant. However, it is noteworthy that these new solvent systems represent greener alternatives to the chlorinated solvents used in the oxidative cleavage of β-hydroxy ethers by RuO4.